Does Prophylactic Replacement of Voice Prosthesis Make Sense? A Study to Predict Prosthesis Lifetime. (28th January 2023) - Heirman, Anne N.; van der Noort, Vincent; van Son, Rob; Petersen, Japke F.; van der Molen, Lisette; Halmos, Gyorgy B.; Dirven, Richard; van den Brekel, Michiel W.M.
Abstract: Objective: Voice prosthesis leakage significantly affects the quality of life of patients undergoing laryngectomy, causing insecurity and frequent unplanned hospital visits and costs. In this study, the concept of prophylactic voice prosthesis replacement was explored to prevent leakages. Study Design: Retrospective cohort study. Setting: Tertiary hospital. Methods: This study included all patients who underwent laryngectomy between 2000 and 2012 in the Netherlands Cancer Institute. Device lifetimes and voice prosthesis replacements of a retrospective cohort were used to calculate the number of needed voice prostheses per patient per year to prevent 70% of the leakages by prophylactic replacement. Various strategies for the timing of prophylactic replacement were considered: adaptive strategies based on the individual patient's history of replacement and fixed strategies based on the results of patients with similar voice prosthesis or treatment characteristics. Results: Patients used a median 3.4 voice prostheses per year (range, 0.1‐48.1). We found high inter‐ and intrapatient variability in device lifetime. When prophylactic replacement is applied, this would become a median 9.4 voice prostheses per year, which means replacement every 38 days, implying >6 additional voice prostheses per patient per year. The individual adaptive model showed that preventing 70% of the leakages was impossible for most patients and only a median 25% can be prevented. Monte‐Carlo simulations showed that prophylactic replacement is not feasible due to the high coefficient of variation (SD/mean) in device lifetime. Conclusion: Based on our simulations, prophylactic replacement of voice prostheses is not feasible due to high inter‐ and intrapatient variation in device lifetime.